Thymidine kinase and deoxycytidine kinase activity in mononuclear cells from antiretroviral-naive HIV-infected patients - Turriziani, Ombretta; Butera, Ornella; Gianotti, Nicola; Parisi, Saverio G; Mazzi, Romualdo; Girardi, Enrico; Iaiani, Giancarlo; Antonelli, Laura; Lazzarin, Adriano; Antonelli, Guido (AIDS (London), 2005)
To evaluate whether an inter-individual variability in the activity of thymidine kinase (TK) and deoxycytidine kinase (dCK), which are involved in the first step of phosphorylation of some nucleoside analogues, exists in antiretroviral-naive, HIV-seropositive patients. Forty-five randomly selected antiretroviral-naive HIV-infected patients were recruited, together with 26 healthy volunteers with no concurrent infection and under no pharmacological treatment. Peripheral blood mononuclear cells (PBMC) were isolated from venous blood and their TK and dCK activities evaluated. CD4 T cells and HIV-RNA were measured in HIV-infected patients, too. There was a broad range of variability in TK activity in HIV-infected individuals. Furthermore, the activity in PBMC was significantly higher in HIV-infected individuals than in healthy volunteers. dCK activity in seropositive patients was significantly lower than in healthy volunteers. A marked inter-individual variability in dCK levels was observed in the HIV-infected group. No correlations were found between TK or dCK activities and plasma viral load, CD4 cell count, sex or age of patients. A marked range of inter-individual variability of TK and dCK activities in PBMC exists in HIV-infected individuals but not in healthy volunteers, indicating that the activity of enzymes with key roles in drug activation could vary greatly from one patient to another. Furthermore, TK expression is greater in HIV-infected individuals than in healthy volunteers. Better understanding of the viral or cellular factors that contribute to this variability, as well as their effect on responses to antiretroviral treatment, may aid optimization of the management of HIV-infected patients.